Gesturing with tangible interfaces for mixed reality - Dias, J.; Santos, P.; Bastos, R. (GW 2003: Gesture-based communication in human-computer interaction, Conference proceedings, 2004)
This work reports a Tangible Mixed Reality system that can be applied to interactive visualisation scenarios in diverse human-assisted operations, such as in training, troubleshooting and maintenance tasks of real equipments, or in product design scenarios in various sectors: Architecture, Automotive or Aerospace. With the system, the user is able to intuitively interact with an augmented version of real equipment, in normal working settings, where she can observe 3D virtual objects (in the VRML 97 format) registered to the real ones. Totally sensor-less Tangible Interfaces (Paddle and Magic Ring), are used to aid interaction and visualisation tasks in the mixed environment. By means of Tangible Interfaces gesturing recognition, it is possible to activate menus, browse and choose menu items or pick, move, rotate, and scale 3D virtual objects, within the user’s real working area or transport the user from Augmented Reality to a fully Virtual Environment and back.